PEMANFAATAN AIR SUNGAI ALALAK UTARA OLEH MASYARAKAT DI BANTARAN SUNGAI ALALAK UTARA DI KELURAHAN ALALAK UTARA KECAMATAN BANJARMASIN UTARA KOTA BANJARMASIN - Mayang Sari; Sidharta Adyatma; Ellyn Normelani (Universitas Lambung Mangkurat, 2016)
The title of this Research is “The Utilization of the River Side of North Alalak by the peoples on the River Side of North Alalak village North Alalak Regency of North Alalak”. The purpose of this research is to knowing the utilization of the river North Alalak for drinks, cooks, baths, washes,ablution, cleans houses and plants watering. The population in this research are all the society who living on the river side of North Alalak. The big sampling taken in this research are 104 family leader as respondents. The technique of this research is Simple Random Sampling. The data that used is Primary Data and Secondary Data. The Primary Data got directly on the field using questioners and secondary data got from government instancy such as BPS, and Regency Head Office. Analyze technique used is percentasion analysis and interval class.The results of this research are drinks in Low class with 0 percent,cooks in Low class with 0 percent, baths in High class with 77 percent,washes in High class with 74 percent, ablution in Low class with 1 percent,cleans houses in High class with 95 percent, plants watering in High class with 92%.Keywords: The Utilization, River Water,Peoples Activity